Does the Fish Rot from the Head? Organised Crime and Educational Outcomes in Southern Italy - Marina Cavalieri; Massimo Finocchiaro Castro; Calogero Guccio (ZBW - Leibniz Information Centre for Economics, 2021)
This paper explores the relationship between the presence of organised crime in local institutions and the educational outcomes in Southern Italy. To this purpose, we have built a contemporary index of Mafia institutional infiltration that proxies the (scale of) values that parents transmit to their children and that are likely to impact on their educational achievements. Furthermore, combining contemporary individual-level educational outcomes with historical data on mafia infiltration, we control for endogeneity concerns through an IV strategy. We find that a standard deviation increase in our indicator of Mafia institutional infiltration leads to a decrease of about 2 percentage points in the outcomes achieved by primary school students undertaking the INVALSI test for literacy in Southern Italy. Our results are robust to the use of different measures of organised crime, to the inclusion of different sets of controls, different subsamples and to relaxing the exclusion restriction in the IV strategy.
Keywords: 300; Organised crime; Mafia-type organisations; Education outcomes; INVALSI; Investments in education; Italy